Towards an Indigenous Hydropoetics: Human-River Interdependencies in Aboriginal Australian Poetry - Ryan, John Charles (The Trumpeter, 2024)
This article delineates the idea of an Indigenous hydropoetics as an ancestral outlook on rivers grounded in Aboriginal cultural traditions of, and everyday interactions with, rivers. In particular, two features—embodiment and relationality—prove integral to conceptualising Indigenous hydropoetics in response to the hydrological precarities of the present. Recognising rivers' capacity for agency, the idea is developed in relation to contemporary Aboriginal Australian poetry narrating long-standing human interdependencies with rivers. The hydropoetic verse of Jack Davis, Samuel Wagan Watson, and Jeanine Leane reveals embodied relations to—and relational epistemologies of—rivers and their habitats through a focus on Derbal Yerrigan (the Swan River) of Western Australia, Marrambidya Bila (the Murrumbidgee River) of New South Wales, and Maiwar (the Brisbane River) of Queensland, respectively. Their writing integrates Dreaming narratives and elicits river poiesis, while also confronting aquatic conservation urgencies in Australia. Evoking sacred rivers whose origins lie in the Dreaming, their work also presents a medium for reverent listening to the fluvial world. While Leane’s hydropoetics centres on the mediating role of memory—hers and the river’s—Watson’s poetry calls attention to fractured river ecologies in Brisbane's urban environment. For Davis, bodily relationality between humans, plants, and rivers presents a potent means of ecopolitical resistance through multispecies solidarity. Immersed in Aboriginal creation narratives, an Indigenous hydropoetics foregrounds the multidimensional intersections between humans, rivers, and all life, thus energising new imaginings of rivers and encouraging receptivity to their biocultural complexities.